Multiple spotty lesions of the spinal cord in a Chinese patient with human T-lymphotropic virus type 1-associated myelopathy/tropical spastic paraparesis. (March 2018) - Gao, Hongzhi; Ye, Xiang; Cai, Ruowei; Xu, Qiping; Liang, Liping; Izumo, Shuji; Xing, Hui Qin; Kubota, Ryuji
Highlights: The first case of human T-lymphotropic virus type 1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) in China, an area that is non-endemic for HTLV-1, is reported. The patient showed multiple spotty lesions in the cervical spinal cord by MRI. The diagnosis was delayed for 4 years without testing for anti-HTLV-1 antibody. An HTLV-1 serology test should be considered for patients with paraparesis, even in China. Abstract: The case of a Chinese patient with human T-lymphotropic virus type 1 (HTLV-1)-associated myelopathy/tropical spastic paraparesis (HAM/TSP), who showed typical neurological symptoms of the disease, is reported here. Since the presence of anti-HTLV-1 antibody was not investigated, this patient's diagnosis of HAM/TSP was delayed for 4 years. Magnetic resonance imaging revealed multiple spotty lesions in the cervical spinal cord, probably reflecting pathological changes known as perivascular lymphocytic infiltrations of the spinal cord. As this is the first case report of a HAM/TSP patient in China, it is suggested that serological testing for HTLV-1 should be considered in patients with spastic paraparesis even in areas that are non-endemic for HTLV-1.